Tocotrienol and cancer metastasis. (7th March 2016) - De Silva, Leanne; Chuah, Lay Hong; Meganathan, Puvaneswari; Fu, Ju‐Yen
Abstract: Tumor metastasis involves some of the most complex and dynamic processes in cancer, often leading to poor quality of life and inevitable death. The search for therapeutic compounds and treatment strategies to prevent and/or manage metastasis is the ultimate challenge to fight cancer. In the past two decades, research focus on vitamin E has had a shift from saturated tocopherols to unsaturated tocotrienols (T3). Despite sharing structural similarities with tocopherols, T3 strive to gain scientific prominence due to their anti‐cancer effects. Recent studies have shed some light on the anti‐metastatic properties of T3. In this review, the roles of T3 in each step of the metastatic process are discussed. During the invasion process, signaling pathways that regulate the extracellular matrix and tumor cell motility have been reported to be modulated by T3. Although studies on T3 and tumor cell migration are fairly limited, they were shown to play a vital role in the suppression of angiogenesis. Furthermore, the anti‐inflammatory effect of T3 could be highly promising in the regulation of tumor microenvironment, which is crucial in supporting tumor growth in distant organs. © 2016 BioFactors, 42(2):149–162, 2016